Gray matters : the workplace survival guide - Rosner, Bob
"Full of uncommon insight and practical guidance, Gray Matters offers real business wisdom in an action-packed, endlessly entertaining illustrated [cartoons] format that trades cynicism for solutions."--P. 4 of cover.